Trabalho e formação na fronteira: o caso da escola da AJOPAM - Juina - MT - Riscarolli, Eliseu (2002)
The life follows on by the frontier independently from the actions of the State, however its presence is merely to guarantee certain basic conditions of the workers who, voluptuaries or stimulated by the official programs of settling, use to go disclosing the forest and affirming, "unconsciously" the condition of the Brazilian State. The Present work has as object to study the actions undertaken by the Organized Association for Mutual Aid - AJOPAM - in the northwest of Mato Grosso according to what refers to the developed organizational and pedagogical process from 1986, more specifically around those that agglutinated the formation and professional qualification of the agricultural workers, configured as the School of Agriculturists Technician that started working in the 1997. Giving more importance for the professional preparation of the workers, installing some new conceptions and relation between the men and the nature, after all when they transform the landscape imagining that the natural resources will be forever abundant. It has passed less than twenty years of the occupation that was stimulated by the State in the region and what we see is the indifference of the public politics, principally related to the environment which makes us to incorporate it in a different pedagogy of the land, not because of the tendencies of the moment, that could be pos modern, but as a possibility for the future generations to have survival conditions. In this way, the fights of the agricultural workers, women or men, are not established in the contradiction of the way of working but on the forms that it is organized there and that they are results of the workers actions and their social movements like the AJOPAM that shows their new perspectives of working, dreaming, utopias, frustrations and desires to see, in a brief future, better conditions of education, culture, health, transport and social providence.